Oculto sendero - Fortún, Elena (Fortún, Elena. Biblioteca Elena Fortún., 2016)
Oculto sendero, the unpublished novel and literary testament of Elena Fortun (1885-1952) finally comes to light. Fortun wrote this autobiographical novel during her exile in Argentina under the pseudonym Rosa Maria Castaños. The protagonist is María Luisa Arroyo, painter and preteen who wants to dress as a sailor. The path of her life is to the understanding of her homosexuality, a path that progresses evenly to the knowledge and realization of the artistic and intellectual potential of the protagonist. After a childhood narrated in the purest Fortun style, María Luisa Arroyo will leave behind the dictates of conventional femininity to enter an inevitable and also heartbreaking modernity. Set in pre-1936 Spain, Oculto sendero offers a unique and necessary portrait of the intimacy and struggle of an exceptional woman.